PROBLEMS IN EVALUATING CONCLUSIONS IN PROBABLE FORM - Abdullaev, Rustam (Универсальная индексная библиотека Евразийского журнала права, финансов и прикладных наук, 2023)
The article discusses the special knowledge and features and features, the goals and significance of the conclusion of a forensic expert, the existing problems in assessing the expert's opinion, as well as conclusions in a probable form. Based on the scientific views of forensic scientists, analysis of investigative and expert practice, proposals were made about the important features of the expert's conclusion as evidence, equal legal force of his conclusions in a categorical and probable form, as well as the need to consider such conclusions within the evidence system.